Enhancing Maharah Istima’ Through Roleplay and Focus Group Discussion: Implications for AI-Supported Language Learning - Mushthafa Shadiq Al-Rafi'i; Nissa Media Utami; Anneu Rosyanti Suryana; Rizzaldy Satria Wiwaha (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Arabic language learning in Indonesia continues to face challenges, particularly in developing students’ Maharah Istima’ (listening skills), which are often hindered by limited vocabulary, rapid speech input, and the dominance of passive instructional approaches. This study aims to examine the effectiveness of integrating Roleplay and Focus Group Discussion (FGD) in improving students’ listening ability within a classroom context. This research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of 20 fifth-grade students at Al-Irhaam Global Islamic School Bandung, divided into an experimental group receiving Roleplay and FGD-based instruction and a control group receiving conventional audio-based instruction. Data were collected through pre-test and post-test and analyzed using Shapiro-Wilk normality test, homogeneity test, paired sample t-test, and N-Gain analysis. The findings indicate a statistically significant improvement in the experimental group (p < 0.05), with mean scores increasing from 72.0 to 88.0 and an N-Gain value of 0.63 (moderate category). Compared to the control group, the results suggest that interactive and collaborative learning activities contribute more effectively to the development of listening skills. These findings highlight the pedagogical potential of integrating Roleplay and FGD in promoting active engagement and deeper processing of language input. While this study is limited to a small-scale classroom context, it offers practical implications for designing interactive listening instruction and suggests opportunities for future integration with AI-supported language learning tools.